Therapeutic Effects of Aqueous Extracts of Petroselinum Sativum on Ethylene Glycol-Induced Kidney Calculi in Rats - Saeidi, Jafar; Bozorgi, Hadi; Zendehdel, Ahmad; Mehrzad, Jamshid (Urology Journal, 2012)
Purpose: To investigate the therapeutic effects of the aqueous extract of Petroselinum Sativum aerial parts and roots on kidney calculi. Materials and Methods: Thirty-six male Wistar rats were randomly assigned into 6 groups and treated for 30 days. Group A served as normal control and group B received 1% ethylene glycol in drinking water. Groups C, D, E, and F received 1% ethylene glycol from day 0 and were used as the treatment subjects. Rats in groups C and D received 200 and 600 mg/kg body weight of aerial parts aqueous extract, respectively, and those in groups E and F received 200 and 600 mg/kg body weight of root aqueous extract in drinking water, respectively, from the 14th day of the experiment. Results: On the 14th and 30th days of the experiment, serum level of magnesium (1.71 ± 0.12 and 3.81 ± 0.25, respectively) decreased significantly while serum level of calcium (10.45 ± 0.26 and 11.33 ± 0.18, respectively) increased significantly in group B compared with the control group (14th day: magnesium = 2.87 ± 0.17 and calcium = 8.80 ± 0.00 and 30th day: magnesium = 6.01 ± 0.00 and calcium = 8.30 ± 0.22; P < .001). In the treatment groups of C, D, E, and F, the number of deposits decreased significantly compared with group B on the 30th day (P < .001). The weight of the kidneys increased significantly in group B (2.01 ± 0.17) compared with the control group (1.52 ± 0.07) and decreased significantly in treatment groups (P < .05). Conclusion: Petroselinum Sativum has a therapeutic effect on calcium oxalate stones in rats with nephrolithiasis and reduces the number of calcium oxalate deposits.